URGENSI PENALARAN DAN PENEMUAN HUKUM BAGI PEJABAT TATA USAHA NEGARA DIKABUPATEN NIAS UTARA DALAM PEMBENTUKAN DAN PENGEMBANGAN KOPERASI DESA MERAH PUTIH. - Faahakhododo Telaumbanua; Rahmayanti Rahmayanti; Eko Gunarso Tamba; Liberkah Gulo (JOSH: Journal of Sharia, 2026)
The establishment and development of the Merah Putih Village Cooperative (KDMP) in North Nias Regency requires sound legal reasoning and legal research from local State Administration (TUN) officials. This study aims to analyze the urgency of legal reasoning and legal research for TUN officials in supporting the establishment and development of the KDMP. The research method used combines normative-empirical methods with qualitative and legal analysis, along with case study and literature approaches. The results indicate that legal reasoning and legal research are crucial for TUN officials to create legal certainty, reduce conflict, increase accountability, and overcome legal difficulties in establishing and developing the KDMP in the village.